A phase IB/IIA study of remestemcel‐L, an allogeneic bone marrow‐derived mesenchymal stem cell product, for the treatment of medically refractory ulcerative colitis: an interim analysis. (19th July 2022) - Lightner, Amy L.; Dadgar, Neda; Matyas, Caroline; Elliott, Kavita; Fulmer, Clifton; Khaitan, Neha; Ream, Justin; Nachand, Douglas; Steele, Scott R.
Abstract: Aim: There have been no studies into the direct injection of mesenchymal stem cells (MSCs) for luminal ulcerative colitis (UC). Our aim was to investigate the efficacy of MSCs delivered locally via endoscopic delivery, as is done in the setting of perianal disease, to treat the local site of inflammation directly. Method: A phase IB/IIA randomized control clinical trial of remestemcel‐L, an ex vivo expanded allogeneic bone marrow‐derived MSC product, at a dose of 150 million MSCs versus placebo (2:1 fashion) delivered via direct injection using a 23‐gauge sclerotherapy needle at the time of colonoscopy was designed to assess the safety and efficacy of endoscopic delivery of MSCs for UC. The main outcome measures were adverse events, Mayo score and Mayo endoscopic severity score at 2 weeks, 6 weeks and 3 months post‐MSC delivery. Results: Six patients were enrolled and treated; four received MSCs and two placebo. All had been on prior anti‐tumour necrosis factor or anti‐integrin therapy. There were no adverse events related to MSCs. In the treatment group ( n = 4), the Mayo endoscopic severity score decreased in all patients by 2 weeks after MSC delivery. At 3 months, all patients were extremely satisfied or satisfied with their MSC treatment based on the inflammatory bowel disease patient‐reported treatment impact (IBD‐PRTI), and treatment response was described as excellent or good in all patients. In the control group ( n = 2), the Mayo endoscopic severity score did not increase as a result of being off alternative therapy. At 3 months, patients were dissatisfied according to the IBD‐PRTI, and treatment response was poor or unchanged. Conclusion: MSCs may offer a safe therapeutic option for the treatment of medically refractory UC. Early data suggest improved clinical and endoscopic scores by 2 weeks after MSC delivery.